Early cytomegalovirus‐specific T‐cell response and estimated glomerular filtration rate identify patients at high risk of infection after renal transplantation. Issue 2 (29th March 2016) - Leone, F.; Gigliotti, P.; Mauro, M.V.; Lofaro, D.; Greco, F.; Tenuta, R.; Perugini, D.; Papalia, T.; Mollica, A.; Perri, A.; Vizza, D.; La Russa, A.; et al.
Abstract: Background: Assessing the risk of cytomegalovirus (CMV) viremia in kidney transplant recipients (KTR) may be helpful to indicate in which patient it is worth starting antiviral treatment during preemptive strategy. Methods: In 40 CMV‐seropositive KTR preemptively treated with ganciclovir, we used interferon (IFN)‐γ ELISpot test to evaluate whether monitoring T cells directed against phosphoprotein (pp) 65 and immediate early (IE)‐1 antigens could predict the onset of viremia. Results: CMV viremia occurred in 24 patients (60%) within 120 days after transplantation. Non‐viremic patients had higher anti‐pp65, anti‐IE‐1 T cells, and estimated glomerular filtration rate (eGFR) in the first 90 days after transplantation. At logistic regression, anti‐pp65, anti‐IE‐1 T cells, and eGFR measured at day 30 were significantly associated with CMV infection. Cutoff values of 15 spot‐forming cells (SFCs)/200, 000 peripheral blood mononuclear cells (PBMCs) for anti‐IE, 40 SFCs/200, 000 PBMCs for anti‐pp65, and 46.6 mL/min/1.73 m 2 for eGFR, respectively, predicted the risk of CMV infection with high sensitivity and specificity (area under the receiver operating characteristic curve >0.75). Using a classification tree model, we identified as high‐risk patients those showing anti‐pp65 <42 SFCs/200, 000 PBMCs and eGFR <62 mL/min/1.73 m 2, as well as anti‐pp65 ≥42 and anti‐IE‐1 <6.5 SFCs/200, 000 PBMCs. Conclusion: Monitoring CMV‐specific T‐cell responses and eGFR in the first month post transplant can identify patients at high risk of CMV infection, for whom preemptive antiviral therapy is recommended.